Penyiaran Islam dari Sisi FItrah Manusia - Saepuloh, Uwoh (Prophetica, 2009)
Islamic broadcasting its reality is gone upon on human character, since Islamic broadcasting first time make discreet person as object it. Between character characteristic that constitutes argument this character get as been detailed: (1) that Islamic broadcasting realize balance among physical and mental in both individual and communitys life, (3) stemmed Islamic broadcastings of Islamic laws that comprehensive for all type and all human development phase, (5) Broadcasting Islamizing to notice human nature characters